Polycarpon moreiranum, nueva especie de Caryophyllaceae endémica de Chile - Muñoz-Schick, Mélica; Moreira-Muñoz, Andrés; de Trenqualye, Alain (Gayana Botánica, 2016)
During a scientific prospection to the Guatulame site in the Coquimbo Region, we have found a new species of Polycarpon, here described. This new species is, together with P. coquimbense Gereau y Martic., the second Chilean endemic species of the genus, with a known distribution also restricted to the Andes of Coquimbo Region.